A time for play: Interstitial time, Invest/Express games, and feminine leisure style. (January 2018) - Chess, Shira
Games such as FarmVille and other casuals played on social networks and mobile devices have recently become increasingly popular. Research on Social Networking Games (SNGs) often focuses on the "social" aspects—how this newer style of games engenders social relationships from disparate locations. This essay examines the genre of gaming in terms of their industry category, "Invest/Express Games." Using the Invest/Express label as a means of rethinking the role of interstitial time, this essay proposes that the gaming style taps in to what can be understood as "feminine leisure style." In many ways, the significance of Invest/Express embodies a shift toward a feminization of popular video games.